2042-LB: Hypoglycemia Performance of a Continuous Intradermal Glucose Sensor - BISHOP, JEFFREY J.; VANDENBERG, AMY L.; BHAVARAJU, NARESH C.; YANG, RICH; WANG, LIANG; CAI, ALBERT; TANGNEY, JARED R. (Diabetes (New York, N.Y.), 2025)
Introduction and Objective: Continuous Glucose Monitoring (CGM) accuracy in hypoglycemia is critical for people with diabetes on intensive insulin therapy (IIT). FDA special controls define iCGM criteria, including sensor accuracy at glucose levels under 70 mg/dL (>85% within 15 mg/dL). Biolinq has developed an intradermal sensor with accurate glucose measurements from the intradermal interstitial fluid. Methods: Biolinq conducted a clinical study in 202 subjects (67% Type 1 DM, 20% Type 2 DM on IIT, and 13% Type 2 DM on basal or no insulin) wearing an intradermal sensor. Glucose levels were manipulated in clinic to gather data in the hypoglycemic range and venous blood was obtained every 15 minutes for 10 hours and analyzed with YSI (YSI Inc, Yellow Springs, Ohio) 2300 Stat Plus (743 matched pairs below 70 mg/dl). Results: With a prospective factory calibrated algorithm, accuracy in hypoglycemia was 8.1 mg/dL (MAD) with 88.3% (656/743) of sensor glucose values within 15 mg/dL of corresponding time matched YSI values, while 97.7% of these sensor measurements were within 40 mg/dL. Conclusion: The study data shows that intradermal continuous glucose sensors can perform accurately in hypoglycemia.